University students' perception of workload: The challenges and vagaries of assessment. - Dixon, Kathryn; Scott, Shelleyann; Dixon, Robert (AARE Inc, 2007)
Evaluating the academic performance of university students is a problematic area which frequently highlights differences in perspective between students and lecturers. This study explored university students' concerns with workload and assessment. The research utilises student questionnaires and in-depth focus group interviews. The questionnaire data encompassed individual student responses over a period of six years and were analysed using statistical quantitative software. Four separate focus group interviews were conducted with first, second and third year students to explore students' insights on issues that had emerged from the questionnaire data. Students indicated that workload was a significant issue along with assessment. Unit requirements were frequently vague with few marking guidelines and little or no feedback being provided to inform progress. Group assignments were over-utilised in the curriculum and were frequently poorly structured and monitored. The over emphasis on memorisation with low cognitive assessment tasks resulted in boredom and dissatisfaction. The lessons learned from this study provide insights to professional developers within the university context. This research is part of larger study focused on supporting positive educational changes within the university context and is of particular relevance due to the ongoing demands for increasing the quality of teaching and learning.